Upaya Meningkatkan Keterampilan Motorik Halus melalui Media Loose Parts pada Anak Usia 5-6 Tahun - Latifah Laila Khairunisa; Ika Budi Maryatun; Aprilia Dwi Wijayanti (Universitas Alma Ata, 2026)
This study aims to improve fine motor skills in children aged 5â€“6 years at TK Negeri 6 Yogyakarta through the use of loose parts media. The research employed a Classroom Action Research (CAR) approach using the model developed by Kemmis and McTaggart, which was carried out in two cycles of action. The subjects of this study were children in Group B at TK Negeri 6 Yogyakarta, aged between 5 and 6 years. Data were collected through observation and documentation techniques, and analyzed using both qualitative descriptive and quantitative methods.The findings indicate that the gradual use of loose parts media significantly enhanced the children’s fine motor skills. In the pre-action stage, the fine motor skills were at 42.16%. After Cycle I, there was an increase to 51.31%, and a more substantial improvement was observed in Cycle II, reaching 82.35%.This improvement was achieved through a series of action steps: (1) the teacher introduced the loose parts media to be used, (2) the children observed the various forms and functions of the materials, (3) the children engaged in creative activities with guidance from the teacher, (4) the teacher encouraged the children to tidy up the materials after use, and (5) the teacher and children conducted a reflection on the play process and their creations. In conclusion, the use of loose parts media is proven to be effective in enhancing fine motor skills in early childhood education settings. Keywords: early childhood, fine motor skills, loose parts